2014
DOI: 10.1016/j.injury.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-efficacy for managing recovery in the trauma intensive care population: A prospective cohort study

Abstract: Citation: Connolly, F. R., Aitken, L. M., Tower, M. and Macfarlane, B. (2014). Factors associated with self-efficacy for managing recovery in the trauma intensive care population: A prospective cohort study. Injury, 45(1), pp. 272-278. doi: 10.1016Injury, 45(1), pp. 272-278. doi: 10. /j.injury.2013 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
(11 reference statements)
2
8
1
Order By: Relevance
“…SE is associated with motivation; this could mean that individuals with a high SE also are motivated and thus have performed more rehabilitation exercises. 23 Hand grip strength in the study group was 58% compared with the uninjured side three months postoperatively; this is somewhat lower than what was found in a study by Landgren, 24 who found a grip strength of 69% 3 months postoperatively. However, these patients were treated with volar locking plates or fragment-specific plates so the cohorts are not entirely comparable.…”
Section: Discussioncontrasting
confidence: 57%
“…SE is associated with motivation; this could mean that individuals with a high SE also are motivated and thus have performed more rehabilitation exercises. 23 Hand grip strength in the study group was 58% compared with the uninjured side three months postoperatively; this is somewhat lower than what was found in a study by Landgren, 24 who found a grip strength of 69% 3 months postoperatively. However, these patients were treated with volar locking plates or fragment-specific plates so the cohorts are not entirely comparable.…”
Section: Discussioncontrasting
confidence: 57%
“…Self-efficacy is defined as a person's belief (confidence) in his or her ability to perform a set of actions; the stronger these beliefs are in a person, the more likely he or she will initiate and continue activities that aid the attainment of a positive outcome. [9][10][11] Although generally thought of as being domain-specific, the concept of general self-efficacy represents a broad and stable confidence in one's ability to deal with different demanding situations. 12 Self-efficacy for managing chronic disease (SECD) is a patient's confidence in their management of different aspects of chronic diseases, such as symptom control, role function, emotional functioning and communicating with physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Related to the influence of self-perceived health status in general self-efficacy, we did not find studies that could analyze this relation directly, but some of them do that indirectly. For example, the study by Connolly et al (2014) showed that one of the factors more associated with self-efficacy in ill people who are recovering from severe traumas was the disease perception. In other words, a better perception of the real characteristics of the disease are positively associated with higher levels of self-efficacy in those sick people.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature has made a strong association between general self-efficacy and other psychosocial factors. Examples of these dimensions are the perceived social support (Bonsaksen, Lerdal, & Fagermoen, 2012;Warner et al, 2011), anxiety (Tahmassian & Moghadam, 2011), the disease perception and psychological suffering (Connolly et al, 2014), and depression (Dilorio et al, 2006;Tahmassian & Moghadam, 2011;Qian & Yuan, 2012). In this context, the goal of this paper is to identify the psychosocial predictors in general self-efficacy in elderly patients of a Brazilian Health Basic Unit.…”
Section: Introductionmentioning
confidence: 99%